Case report: Accessory cavitated uterine malformation: A diagnostic dilemma - Karma Tenzing Bhutia; Ruchi Gupta; Ragunath Ponnusamy (Radiology Case Reports, 2025)
Accessory cavitated uterine malformation (ACUM) is a commonly misdiagnosed Mullerian anomaly characterized by the presence of a cavitated, well circumscribed lesion in an otherwise normal uterus showing presence of endometrial gland and stromal components. Commonly presenting as recurrent abdominal pain with dysmenorrhea in young females, their management is often delayed due to misdiagnosis on imaging. Here, we present the case of Accessory cavitated uterine malformation (ACUM) in a 21-year-old nulliparous female presenting with complaints of chronic abdominal pain with periodic dysmenorrhea who was managed with laparotomic excision of the cavity.